The Factors Affecting Behaviour Based Safety (BBS) Implementation in Oil and Gas Industry - Antonio Galis, Amanda; Hashim, Norfashiha; Ismail, Faridah; Mohd Yusuwan, Norazian (International Journal of Engineering and Technology, 2018)
The application of Behaviour-Based Safety (BBS) in the oil and gas industry is facing a severe challenge that safety performance may decline when BBS intervention is removed, due to the dynamic and transitory nature of working area and workforce. This research investigates the factors affecting the implementation of Behaviour-Based Safety (BBS) approach in Oil and Gas Industry. Seven oil and gas companies practicing BBS had been chosen for case study. These companies has been implementing BBS as part of the safety exercise from 2 to 20 years. The findings show that implementation of BBS started by the request from the client. Seven challenges of implementation BBS emerged during the interview that is data management, top management commitment, employee acceptance towards program, organizational safety culture and financial barrier. While, the factor that influences the implementation of BBS is the organization commitment, top management level, training and understanding of workers toward BBS are the factors that affect the implementation of BBS in oil and gas industries.Â Â